Pengaruh Return on Asset, Current Ratio, dan Debt to Asset Ratio terhadap Firm Value dengan Firm Size sebagai Variabel Moderating: (Studi Kasus Pada Perusahaan Sub Sektor Perdagangan Besar Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Rachmad Reza F; Jufrizen Jufrizen; Muis Fauzi Rambe (Politeknik Ganesha Medan, 2023)
This study aims to determine how the effect of Return On Assets, Current Ratio, and Debt To Asset Ratio on Firm Value and how the role of Firm Size as a moderating variable in the effect of Return On Assets, Current Ratio, and Debt To Asset Ratio on Firm Value in Sub-Companies. Large Trading Sector Listed on the Indonesia Stock Exchange 2016-2020. This research approach is an associative approach, where the total company population is 51 companies with a sampling technique, namely Purposive Sampling so that a sample of 10 large trading sub-sector companies are obtained which are listed on the Indonesia Stock Exchange in 2016-2020, and the financial statements taken are secondary data. , which is obtained from the www.idx.co.id website, and the data that has been collected will be analyzed using Multiple Regression Analysis & Moderating Regression Analysis (MRA) accompanied by partial hypothesis testing and coefficient of determination. data processing using IBM SPSS Statistic 21. The results show that Return On Assets has a significant effect on Firm Value, Current Ratio has an insignificant but not significant effect on Firm Value, Debt To Asset Ratio has an insignificant effect on Firm Value, Firm Size does not moderate the effect of Return On Assets to Firm Value, Firm Size does not moderate the effect of Current Ratio on Firm Value, Firm Size does not moderate the effect of Debt To Asset Ratio on Firm Value in large trading sub-sector companies listed on the Indonesian stock exchange in 2016-2020. Keywords: Firm Value, Return On Assets, Current Ratio, Debt To Asset Ratio, Firm Size